Knowledge and Practice Regarding HIV among Urban-Rural Men in Bangladesh: A cross sectional study - Sultana, Rezwana; Das, Akkur Chandra (Bangladesh Journal of Infectious Diseases, 2017)
Background: Human immunodeficiency virus (HIV) is one of the very much concerning issues and nearly 30 million people have died because of HIV related causes, which are found mostly low and lower income countries of the world. Objective: The objective of this study was to evaluate knowledge and practice to reduce risk factors of getting HIV among urban and rural men in Bangladesh with the comparative analysis among them. Methodology: This is a cross sectional study among 3997 men (urban=1437 and rural=2560). Frequency and percentage on knowledge and practice to reduce risk factors of getting HIV were counted to describe and also urban-rural significance levels of knowledge and practice issues regarding HIV were tested. Result: Knowledge and practice regarding HIV among urban-rural men were comparatively different where 93.7% urban and 81.9% rural men heard about HIV; 88.3% urban and 74.8% rural men thought that HIV can get by using unsterilized needle or syringe; 90.3% urban and 75.6% rural men thought that unsafe blood transfusions resulted HIV; 78.3% urban and 62.2% rural men use condom always during sex; and these urban-rural knowledge and practice related differences are statistically significant at P<.000. Conclusion: In Bangladesh, there werent massive differences between urban and rural mens knowledge and practice reducing risk factors of getting HIV; but urban men have comparatively more knowledge and practice levels than those of rural men have because of having urban mens higher level of socio-demographic and economic status. Bangladesh J Infect Dis 2015;2(1):3-8